The Development of Pantai Indah Kapuk 2: Social Inequality and Eviction of Salembaran Jati Residents - Shabrina, Nurul (Cities and Urban Development Journal, 2025)
The development of Pantai Indah Kapuk (PIK) 2 has caused social inequality in Salembaran Jati Village because this development project involves the eviction of agricultural land and the relocation of residents to Kampung Jati Baru, creating new challenges in the social aspect. The purpose of this study is to explore the experiences of residents and the inequality of access to primary needs felt by residents of Salembaran Jati Village due to the construction of PIK 2. Using a qualitative descriptive approach, this study refers to the dimensions of sense work and meta criteria of justice in the Good City Form theory by Lynch (1981). The results of the study show that the construction of PIK 2 caused the residents of Salembaran Jati Village to lose their village identity with the loss of agriculture and fishponds as well as their livelihoods as farmers and fishermen, limited access to public facilities, and minimal participation in the development decision-making process. Relocation to Kampung Jati Baru does not meet the basic needs of residents, and it is characterized by poor basic infrastructure and inadequate water quality. In addition, the PIK 2 boundary wall further strengthens the social inequality between PIK 2 residents and residents. This study concludes that the construction of PIK 2, although aimed at creating a modern, environmentally friendly area, still creates significant social inequality. The need for community participation in planning, PIK 2 developers by considering the needs of residents and the central and regional governments that have control over this development.